Comparison of plant species diversity, site index, and mean tree ring width values of different altitudinal zones in Turkish pine stands - Oğuzhan Erfidan; Serkan Özdemir (Turkish Journal of Forestry)
Diversity and productivity have consistently been central topics in forestry research. With the advent of climate change, the need to better understand increasingly scarce natural resources has become critical for sustainable use. In this study, differences in alpha species diversity, site index, and tree-ring widths across three different altitudinal zones were analyzed. Additionally, the relationships between these parameters and environmental variables were analyzed. Initially, a normality test was applied to the data. Due to the failure to meet the normality assumption, non-parametric methods were preferred for data analysis. The Kruskal-Wallis test was applied to identify differences between groups. To determine the relationships of alpha species diversity, site index, and tree-ring width with environmental variables, Spearman correlation analysis was used, focusing on the Shannon and Simpson indices. Our results showed that Shannon and Simpson diversity differ across different altitudinal zones, while no differences were observed in terms of site index and annual ring growth. On the other hand, Bio1 and Bio12 were identified as the most influential variables on diversity. Additionally, there was a relatively low negative correlation between the site index and slope variable and between annual ring growth and the radiation index variable. The findings obtained from this study provided important insights for forestry management. In particular, understanding the effects of altitude-dependent abiotic factors on species diversity and tree ring growth will enable more accurate planning.